METHODOLOGICAL POSSIBILITIES OF SYNONYMS - Shukurov Akhat Akhmatovich (American Journals Publishing, 2024)
In the article, various subtleties of meaning, linguopoetic possibilities of synonyms are described in the example of poetic epics.
Keywords: Synonym, historical epic, speech culture, emotional color, linguopoetic possibility, synonymous relationship.